THE CONCEPT OF CASH FLOW IN MONEY LAUNDERING IN INDONESIA - Itok Dwi Kurniawan; Ismawati Septiningsih (Domus Legalis Cogitatio, 2024)
The development of criminal acts that occur in a country moves with the development of social civilization. One of the criminal acts in the economic sector that has arisen as a result of modern civilization is the crime of money laundering, namely the concealment of assets resulting from a crime so that it appears as if they originate from a legal source. This article will examine the asset tracing strategy which is an effective step in tackling money laundering crimes. The approach used in discussing the problem is a case study. The results of the research in this article are that efforts to trace assets with a fund tracking process need to be developed and adopt existing technological developments. This is to ensure the effectiveness of handling money laundering in Indonesia.